(untitled) (Revista de Artes Marciales Asiáticas, 2019)
This is a report covering the 5th Annual Martial Arts Studies Conference, held in Orange, California (USA) on May 23-24, 2019. There were a total of six parallel sessions comprised of 44 presentations. Although the conference theme was “martial arts, culture, and politics,” the thematic organization extended beyond this premise to all aspects of martial arts as a field of investigation. As a whole, the conference was impressively orchestrated and quite well attended by representatives from around the world and is notable as the first official Martial Arts Studies Research Network event to take place in North America.